Kingdom of heaven [videorecording (DVD)] - Scott, Ridley; Bloom, Orlando, 1977-; Neeson, Liam; Irons, Jeremy, 1948-; Green, Eva, 1980- (20th Century Fox Home Entertainment, 2005)
Orlando Bloom stars as Balian, a young Frenchman in Medieval Jerusalem during the Crusades, who, having lost everything, finds redemption in a heroic fight against overwhelming forces to save his people and fulfill his destiny as a knight.